2001
DOI: 10.1042/bst029a010c
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycans are critical for the organization of the extracellular distribution of Wingless

Abstract: SUMMARYHeparan sulfate proteoglycans are critical for the organization of the extracellular distribution of Wingless

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
241
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(267 citation statements)
references
References 29 publications
23
241
3
Order By: Relevance
“…We have previously shown that Dally plays a role in Wg signaling in the wing disc (Lin and Perrimon, 1999). Furthermore, overexpression of Dlp leads to enhanced extracellular Wg levels in the wing disc (Baeg et al, 2001). Together, these studies implicate possible roles of Dally and Dlp in Wg gradient formation; however, their functions and mechanisms in Wg gradient formation have not been examined by loss-offunction study.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…We have previously shown that Dally plays a role in Wg signaling in the wing disc (Lin and Perrimon, 1999). Furthermore, overexpression of Dlp leads to enhanced extracellular Wg levels in the wing disc (Baeg et al, 2001). Together, these studies implicate possible roles of Dally and Dlp in Wg gradient formation; however, their functions and mechanisms in Wg gradient formation have not been examined by loss-offunction study.…”
Section: Introductionmentioning
confidence: 74%
“…dally P2 is a dally-lacZ line used to visualize dally expression (Nakato et al, 1995). The following UAS constructs were used to overexpress the corresponding transgenes in the posterior compartment of the wing disc: UAS-dlp (Baeg et al, 2001), UAS-dally (Tsuda et al, 1999), UAS-fz and UAS-fz2 (Zhang and Carthew, 1998), and UAS-gfp-arr. UAS-gfp-arr contains the Wg signal peptide (amino acids 1-37) followed by GFP protein and six Myc tags fused with Arr in which the signal peptide (amino acids 1-54) of Arr is deleted.…”
Section: Fly Strainsmentioning
confidence: 99%
See 3 more Smart Citations